Effectiveness and cost-effectiveness of an electronic mindfulness-based intervention (eMBI) on maternal mental health during pregnancy: the mindmom study protocol for a randomized controlled clinical trial - Müller, Mitho; Matthies, Lina; Götz, Maren; Abele, Harald; Brucker, Sara; Bauer, Armin; Graf, Johanna; Zipfel, Stephan; Hasemann, Lena; Wallwiener, Markus; Wallwiener, Stephanie (Trials, 2020)
Mental disorders are common during the peripartum period and may have far-reaching consequences for both mother and child. Unfortunately, most antenatal care systems do not provide any structured screening for maternal mental health. As a consequence, mental illnesses are often overlooked and not treated adequately. If correctly diagnosed, cognitive behavioral therapy is currently the treatment of choice for mental illnesses. In addition, mindfulness-based interventions (MBIs) seem to represent a promising treatment option for anxiety and depression during the peripartum period. Considering the internet’s increasing omnipresence, MBIs can also be offered electronically via a (tablet) computer or smartphone (electronically based MBI = eMBI).